Coloring hot-dip galvanization of steel samples in industrial zinc-manganese baths - Godzsák, Melinda; Levai, Gabor; Vad, Kalman; Csik, Attila; Hakl, Jozsef; Kulcsar, Tibor; Kaptay, Gyorgy (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
Colored hot dip galvanization of various steel samples was realized in an industrial bath containing 738 kg of a Zn-Mn liquid alloy at 450 oC. Zinc was alloyed in three steps to reach 0.1, 0.15 and 0.2 w% of Mn in liquid zinc, and galvanization of 9 different steel samples was performed in all three baths. The obtained colors change in the sequence blue – yellow – pink – green with increasing the Mn-content of the bath and with increasing the wall thickness of the steel samples. The results are analyzed by GD-OES and SNMS techniques. It is shown that depending on the Mn-content and on the wall thickness of the steel the samples are coated by MnO of various thicknesses (in the range between 30 – 230 nm). This layer forms when the samples are removed from the Zn-Mn bath into surrounding air, before the Zn-layer is solidified. Light interference on this thin MnO layer causes the colors of the galvanized coating. Different colors are obtained in different ranges of MnO thicknesses, in accordance with the laws of optics. The minimum Mn-content of liquid Zn is found as 0.025 ± 0.010 m/m% to ensure that the original outer ZnO layer on Zn is converted into the MnO layer. This minimum critical Mn-content is in agreement with chemical thermodynamics.